Screening and Identification of Plant Metabolites against Snake Venom Enzymes using in vitro to in silico Approach - Singh, Pushpendra; Yasir, Mohammad; Shrivastava, Rahul (Indian Journal of Pharmaceutical Education and Research, 2019)
Aim/Background: Snakebites are generally a neglected tropical disease that have harmful impact on thousands of people globally. Although antiserum therapy is the only management available for snakebites, several side effects of this therapy have raised the requirement of an alternative to treat snakebite or boost antiserum efficacy. The present study aimed to provide a scientific explanation for the use of plants extracts in neutralizing snake venom enzymes phospholipase A2, hyaluronidase, DNase and RNase. Materials and Methods: Twelve plant species were selected, which were traditionally used in tribal region of Madhya Pradesh to manage snakebites. Ethanolic and aqueous extracts of these plants were tested for in vitro enzyme neutralization. Further chemical investigation of Dryopteris cochleata rhizome was carried out followed by Molecular docking studies using Glide software tools. Results: D. cochleata extract showed the highest enzyme-neutralizing activity when compared to other plants extracts and exhibited significant antioxidant activity. Molecular docking studies of GC-MS identified that constituent 12-phenyl-2,3,7,8-tetramethoxy-5H-(1)-benzopyrano[4,3-c]isoquinoline had a Glide score of –7.455 and formed hydrogen bonds with ASP 49 amino acid residue of phospholipase A2 molecule. Conclusion: The study concludes that extract of D. cochleata rhizomes inhibit activity of toxic enzymes of snake venom
Keywords: Phospholipase A2; Hyaluronidase; Deoxyribonuclease; Ribonuclease; Dryopteris cochleata